Respuestas
Respuesta dada por:
0
Respuesta:
b) 63º
Explicación paso a paso:
✔ En el Triangulo ADC;
∢A = α + 180 - 4α = 180 -3a
x + 180 - 3a + 3β = 180
x - 3α + 3β = 0
3β - 3α = -x
β - α = -x/3 (1)
✔ En el triangulo AMC;
84 + 180 - 4α + 4β = 180
4β - 4a = - 84
β - a = -84/4
β - a = -21 (2)
igualando (2) y (1);
-x/3 = -21
-x = -63
x = 63º
Adjuntos:
![](https://es-static.z-dn.net/files/d0a/5df0ad7bbb449adbf4269e6f4a31d69a.png)
Preguntas similares
hace 5 años
hace 5 años
hace 8 años
hace 8 años
hace 9 años
hace 9 años